Competências da sustentabilidade na atuação profissional dos egressos do Centro Paula Souza: um estudo de caso - Dourado, Janaína Rute da Silva (2018)
Nowadays, the numerous social, environmental and economic changes that take place on the planet have a rapid impact on the life of individuals, which, some centuries ago could take years, now happens almost instantaneously. However many of these challenges, apparently without possibility or expectation for some sort of resolution we need to just live together, such as environmental problems, deepening economic inequalities. On their side organizations in their great majority try to adopt procedures to minimize possible clashes that certain problems can cause, in turn the competence that could be developed from collaborators turns into just another internal process to be executed and delivered. Considering the importance of skills development and relating it into an existing process, some organizations such as TBL, taking into account the relevance of the objectives of sustainable development, it would be possible to verify in individuals that studied there, pass through an institution of education of technological formation, the Centro Paula Souza, which is oriented by the development of skills and abilities. In this sense, reaching the main objective of this study which is to analyze the relationship between the sustainability content taught in the Management and Business courses of the Centro Paula Souza and its incorporation by the graduates in the exercise of their professional activities. For this, the methodology adopted is characterized by the case study that is divided into: documentary research of the Centro Paula Souza; the analysis of the quantitative research as secondary source "Teacher Training"; and the interviews: with the training coordination of the Center Paula Souza, and with the graduates; finally, the analysis of the data. In this way the results were the documented confirmation that there is a relationship between the pillars of the TBL model and the guidelines of the Center Paula Souza, including the objectives of sustainable development, and the interviews conducted with the graduates, subdivided into blocks of analysis to identify competencies. It was possible to conclude that, based on the findings presented in the interviews that graduates have competencies that are tied to the pillars and intersections of the TBL, making it possible to assign the emergence and development of sustainable skills in these graduates